The longstanding impact of South Korean military culture : representations of South Korean men and women in popular war films and Korean songs - Ang, Ee Suan (Nanyang Technological University, 2022)
South Korean films and popular songs (K-pop) are forms of entertainment that have grown tremendously in scale within the last three decades. Most of the existing literature on these materials have focused on its history and developments as part of Korean popular culture. However, there is a lack of literature that specifically analyses how these forms of entertainment have contributed to the shifts in perceptions of men towards women. It is important to study this shift because South Korean men have been significantly shaped by their military experiences since the twentieth century. By making a parallel comparison between popular war films and K-pop songs, this thesis argues that there are continuing tensions between men’s desire to express their masculinity and the military’s attempts to control men despite the shift from militarization to democratization.